1991
DOI: 10.1002/oms.1210260417
|View full text |Cite
|
Sign up to set email alerts
|

[C6H6, C3H7+]and [C6H7+, C3H6] ion‐neutral complexes intermediate in the reactions of protonated propylbenzenes

Abstract: From the mass-analysed ion kinetic energy spectra of labelled ions, kinetic energy releases and thermodynamic data, it is proved that protonated n-propylbenzene (1) isomerizes into protonated isopropylbenzene (2). It is also shown that the dissociation of the less energetic metastable ions of (2), leading to ]iso-C3H,I+ and (C,H,J+ product ions, is preceded by H exchange. This H exchange involves two interconverting ioweutral complexes [C6H6, is0-C3H7') (2n) and [C6H7+, CjH6] (2a).Y Scheme 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Henri Audier and his group found that gaseous protonated 4‐ tert ‐butylethylbenzene, [ 17 + H] + , undergoes loss of isobutane as the most energetically favorable fragmentation route and they suggested that protonolysis of the C ipso –C α bond gives rise to an ion/neutral complex, [CH 3 CH 2 C 6 H 5 ···C(CH 3 ) 3 + ], as the crucial intermediate (Scheme ) [70,71]. Simple tert ‐butylbenzenium or tert ‐butyltoluenium ions, such as [ 18 + H] + , do not undergo this reaction but rather eliminate benzene/toluene and/or isobutene.…”
Section: Ion/neutral Complexes As Reactive Intermediates During the Fmentioning
confidence: 99%
“…Henri Audier and his group found that gaseous protonated 4‐ tert ‐butylethylbenzene, [ 17 + H] + , undergoes loss of isobutane as the most energetically favorable fragmentation route and they suggested that protonolysis of the C ipso –C α bond gives rise to an ion/neutral complex, [CH 3 CH 2 C 6 H 5 ···C(CH 3 ) 3 + ], as the crucial intermediate (Scheme ) [70,71]. Simple tert ‐butylbenzenium or tert ‐butyltoluenium ions, such as [ 18 + H] + , do not undergo this reaction but rather eliminate benzene/toluene and/or isobutene.…”
Section: Ion/neutral Complexes As Reactive Intermediates During the Fmentioning
confidence: 99%
“…8a) . This behavior is a reliable probe for the intermediacy of the corresponding chain-elongated alkylbenzenium ions, which are well-known to undergo heterolysis of the C ipso -C α bond with selective protonation of the neutral alkene and/or benzene fragments (Leung & Harrison, 1977;Herman & Harrison, 1981;Kuck, 1990aBerthomieu et al, 1991. In the case of ions [21+H] + , ring contraction via ion n (Scheme 12) leads to the n-propylbenzenium ions [22+H] + that eliminate C 3 H 6 and C 6 H 6 in the characteristic ratio of ∼3-5.…”
Section: Ring Contraction/re-expansion Of Alkylcycloheptatrienes-the Interplay Of Bicyclo[321]alkenyl Isomersmentioning
confidence: 99%
“…However, additional and convincing proof for intermediate ion/neutral complexes during the protiolytic gas-phase dealkylation has been obtained recently. Audier and co-workers [45] studied the fragmentation of n-propylbenzene and isopropylbenzene by CI(H20). Under these conditions the MIKE spectrum shows a large signal at m/z 79 due to benzenium ions and a small one at m/z 43 for C3H~ -, formed by elimination of propene and the isopropyl cation, respectively (Scheme 18).…”
Section: Intermediate Ion/neutral Complexesmentioning
confidence: 99%